Hypothalamic lesions in multiple sclerosis. Issue 7 (14th June 2010) - Qiu, Wei; Raven, Sonja; Wu, Jing-Shan; Bundell, Christine; Hollingsworth, Peter; Carroll, William M; Mastaglia, Frank L; Kermode, Allan G
Abstract : Objectives: To determine the frequency of hypothalamic lesions in patients with multiple sclerosis (MS) using conventional MRI (cMRI) protocols. Methods: Brain cMRI (1.5 Tesla) scans of 105 Caucasian patients with classical MS (50 with stable and 55 with more active disease) and 12 patients with longitudinal extensive myelopathy (LEM) were reviewed retrospectively. NMO-IgG antibody was assayed in patients with hypothalamic lesions. Results: Hypothalamic lesions were found in 13.3% of MS patients and in none of the LEM patients. A higher frequency of hypothalamic lesions was found in patients with active MS (18.2%) than in the stable group (8.0%), but this did not reach statistical significance (p=0.13). Patients with hypothalamic lesions also had more lesions in other cerebral structures. None of the LEM patients had hypothalamic lesions. No patients with hypothalamic lesions were positive for NMO-IgG. Conclusions: Hypothalamic lesions in MS are more frequent than previously reported and are not associated with NMO-IgG antibody.